Health Paradigm Shifts in the 20th Century - Jose Miguel DeAngulo; Luz Stella Losada (Health for All Nations, 2015)
The application of systems theory and the study of complexity to medicine and human health allows for a more comprehensive understanding and a more holistic view of what it means to be human. Such application overcomes the limitations of the traditional, fragmented understanding of phenomena and problems based on the mechanistic or Newtonian worldview. It recognizes that phenomena are interrelated, and that individual parts cannot be understood by only focusing on the analysis of their individual qualities. Rather, the individual parts can only be understood in relation to the whole and by being analyzed in the context of their interaction with the whole. The door is opened to previously unimagined models of thinking.In the 20th Century there have been shifts in the paradigms that have governed medicine and human health in the modern western world. There has been a shift from the focus on specific biological analysis and pathological diagnostics to complex human interactions with the environment and with sociopolitical and economic processes. There are complex models of systems in immunology, in neuroscience, and in genetics, as well as complex ways of understanding interactions as in epidemic modeling, in social media technologies, socioeconomic factors, and artificial intelligence.In this paper we describe three paradigms of the health-disease process that in some degree correspond to the historical development of modern medicine and healthcare over the previous century. The oldest paradigm focused on specific disease mechanisms and treatment. This gave way to paradigms that historically were broader and more inclusive, such as "international health". The international health paradigm focused primarily on the control of epidemics across national borders and considered government as the only health actor. However, this perspective has come to be seen as excessively reductionist and excluded many critical components essential to a robust understanding. The old "international health" has in turn been replaced by the paradigm of "global health" that exercises more comprehensive claims, and paved the way for emerging paradigms of complexity in the 21st Century.